2000
DOI: 10.1161/01.cir.101.20.2349
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Angiotensin-1 Receptor Antagonism Reverses Endothelial Dysfunction in Atherosclerosis

Abstract: The results of the present study indicate that inhibition of the AT(1) receptor in patients with atherosclerosis reverses endothelial dysfunction by improving NO availability and therefore may have long-term therapeutic benefits.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
117
0
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 182 publications
(123 citation statements)
references
References 34 publications
5
117
0
1
Order By: Relevance
“…7 The increase of superoxide formation in the intimal layer induces endothelial dysfunction via the reduction of nitric oxide synthesis from endothelial cells. 24 In this study, the high-cholesterol diet significantly reduced relaxation induced by acetylcholine, an endothelium-dependent vasodilator, suggesting that the vascular tissues of atherosclerotic lesions show an endothelial dysfunction, which is the first step in the development of atherosclerotic plaque. The acetylcholine-induced relaxation in those monkeys fed a high-cholesterol diet was, howJournal of Human Hypertension ever, significantly improved by olmesartan.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…7 The increase of superoxide formation in the intimal layer induces endothelial dysfunction via the reduction of nitric oxide synthesis from endothelial cells. 24 In this study, the high-cholesterol diet significantly reduced relaxation induced by acetylcholine, an endothelium-dependent vasodilator, suggesting that the vascular tissues of atherosclerotic lesions show an endothelial dysfunction, which is the first step in the development of atherosclerotic plaque. The acetylcholine-induced relaxation in those monkeys fed a high-cholesterol diet was, howJournal of Human Hypertension ever, significantly improved by olmesartan.…”
Section: Discussionsupporting
confidence: 49%
“…23,24 In the intimal layer of atherosclerotic lesions, activated macrophages induce superoxide formation via the activation of 12-or 15-lipoxygenases. 23 It is observed that smooth muscle cells activated by A II also induce NAD(P)H-dependent oxidases, which promote superoxide formation.…”
Section: Discussionmentioning
confidence: 99%
“…28 In addition, both treatments prevent increased NO inactivation due to oxygen radicals by reducing Ang II type 1-receptor-dependent activation of the oxidant enzyme NADPH oxidase and enhancing EC-SOD activity. 29 Furthermore, an Ang II infusion reportedly resulted in increased superoxide anion production and NADPH-dependent oxidase activity, 30 leading to endothelial dysfunction in animal experiments, 31 though endothelial responses were restored by treatment with superoxide dismutase or ARB. 31 Recently, an improvement of endothelial dysfunction in hypertension has been reported to be associated with ACE2, a newly recognized homolog of ACE.…”
Section: Discussionmentioning
confidence: 99%
“…29 Furthermore, an Ang II infusion reportedly resulted in increased superoxide anion production and NADPH-dependent oxidase activity, 30 leading to endothelial dysfunction in animal experiments, 31 though endothelial responses were restored by treatment with superoxide dismutase or ARB. 31 Recently, an improvement of endothelial dysfunction in hypertension has been reported to be associated with ACE2, a newly recognized homolog of ACE. ACE2 converts Ang II to angiotensin-1-7 (Ang- (1-7)), which increased NO release from endothelial cells through its receptor Mas, thus resulting in vasodilation.…”
Section: Discussionmentioning
confidence: 99%
“…The technique has been described in detail previously. 18 Briefly, studies were performed in a temperature-controlled room, and brachial diameter was measured above the antecubital fossa in the non-dominant arm using an 11 MHz high resolution ultrasound transducer (Acuson Inc., Malvern, PA, USA). Flow-mediated vasodilation (FMD) was determined by inflating a BP cuff on the forearm to 4200 mm Hg for 5 min, deflating rapidly, and recording brachial diameter at 1 min after onset of hyperaemia.…”
Section: Measurement Of Endothelial Functionmentioning
confidence: 99%